Obravnava samomorilno ogroženega pacienta - Bregar, Branko (Obzornik zdravstvene nege, 2012)
Introduction: The treatment of suicidal patients in clinical practice is a demanding task and responsibility, reaching beyond the doors of psychiatric institutions. The suicide rate in Slovenia is above the average suicide prevalence rates in Europe and therefore deserves our special attention. Health professionals should have adequate knowledge for effective and timely intervention. According to the available data, several patients related their feelings to health professionals and sought medical help before committing suicide. The purpose of this article is to present some strategies for reducing this serious public health threat as practiced in Slovenia and abroad, and to recommend some new ones. Methods: A review of existing literature in the Slovene and English language was conducted using the key words 'samomor' and 'suicidal, patient, nursing, care, psychiatry'. The digital archive of the Slovenian Nursing Review and the Science Direct Database were reviewed for the relevant research. Discussion and conclusion: Slovenian authors are primarily focused on the relationship of nursing care providers with suicidal patients. Foreign authors commonly widen their research to more cost-effective strategies of suicide prevention. Nursing of suicidal patients should not be limited only to the safety of the patients butalso to the provision of help and socio-therapeutic support for a successful return to normal life. The factors that determine the establishment of a successful therapeutic relationship are empathy, non-possessive closeness and genuineness. Nursing professionals should therefore acquire adequate skills for more autonomous work in this field.
Keywords: medicinske sestre; nurses; nursing; preprečevanje samomorov; suicide prevention; zdravstvena nega